Real-time monitoring of proton exchange membrane fuel cell stack failure - Wu,B; Parkes,MP; de,Benedetti L; Marquis,AJ; Offer,GJ; Brandon,NP (Journal of Applied Electrochemistry, 2016)
Uneven pressure drops in a 75-cell 9.5-kWe protonexchange membrane fuel cell stack with a U-shaped flowconfiguration have been shown to cause localised flooding.Condensed water then leads to localised cell heating, resultingin reduced membrane durability. Upon purging of the anodemanifold, the resulting mechanical strain on the membranecan lead to the formation of a pin-hole/membrane crack and arapid decrease in open circuit voltage due to gas crossover.This failure has the potential to cascade to neighbouring cellsdue to the bipolar plate coupling and the current densityheterogeneities arising from the pin-hole/membrane crack.Reintroduction of hydrogen after failure results in cell voltageloss propagating from the pin-hole/membrane crack locationdue to reactant crossover from the anode to the cathode, giventhat the anode pressure is higher than the cathode pressure.Through these observations, it is recommended that purging isavoided when the onset of flooding is observed to preventirreparable damage to the stack.